0071 A Mexican Spanish Version of the Circadian Energy Scale. (25th May 2022) - Valencia, Dora; Begay, Tommy; Granados, Karla; Delgadillo, Marcos; Ghani, Sadia; Molina, Patricia; Alfonso-Miller, Pamela; Fernandez, Fabian-Xosé; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Circadian health is increasingly recognized for the contributions it makes to general health. Few instruments assessing circadian rhythms have been translated into Spanish, however. The present study describes a Spanish translation of the Circadian Energy Scale (CIRENS). The instrument was designed according to the language norms of those living along the US-Mexico border by a bilingual research team. The CIRENS was completed by both English and Spanish speaking border residents, in their preferred language. Methods: Data were collected from a sample of N=100 individuals of Mexican descent living in Nogales, Arizona. CIRENS is a 2-item scale that assesses chronotype by examining overall energy level in the morning and evening. Translation of the instrument into Spanish was done according to the following process: (1) a bilingual study team member attempted an initial translation; (2) a bilingual community member edited the translation; (3) a certified medical translator edited the revision; (4) a focus group of N=5 bilingual community members made further contextual edits; (5) a back-translation was performed; (6) an additional bilingual focus group examined the final version for compatibility; and (7) the medical translator certified the accuracy of the final version. T-tests examined differences between those who completed the measure in Spanish vs English. Results: Of the N=100 survey respondents, N=42 completed the CIRENS in Spanish. No significant differences were observed in overall chronotype determination between those who took the Spanish versus English version (p=0.22) of the instrument. As a continuous score, the respondents in Spanish demonstrated slightly more morningness (p=0.01). Per the individual items, no differences were seen for evening energy levels (p=0.22), but Spanish respondents reported slightly higher morning energy scores (2.76 vs 2.17, p=0.008). Conclusion: The individuals that completed the CIRENS in Spanish reported higher morning energy scores but no significant differences in chronotype. Future studies can use the Spanish CIRENS to evaluate circadian factors across cultural/linguistic groups. Support (If Any):